Identifikasi Risiko Rantai Pasok Selada Baby Romaine di PT ABC - Hafidz, Rheina; Syamsiyah, Nur (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Lettuce is a plant that can be grown well with the hydroponic method and is widely developed by small or large scale hydroponic farmers because it has a relatively large market potential. PT ABC is an agribusiness company that produces baby romaine lettuce and distributes it to many consumers. However, the supply quantity of baby romaine lettuce produced by the company is always erratic. This can raise risks that can occur in the baby romaine lettuce supply chain at PT ABC. This study aims to identify the risks that arise in the supply chain of baby romaine lettuce. The research method used is a qualitative method using descriptive analysis. The results showed that there were 16 risk events that occurred in the baby romaine lettuce supply chain at PT ABC.